2018
DOI: 10.1140/epjc/s10052-018-5651-1
|View full text |Cite
|
Sign up to set email alerts
|

Status of the charged Higgs boson in two Higgs doublet models

Abstract: The existence of charged Higgs boson(s) is inevitable in models with two (or more) Higgs doublets. Hence, their discovery would constitute unambiguous evidence for new physics beyond the Standard Model (SM). Taking into account all relevant results from direct charged and neutral Higgs boson searches at LEP and the LHC, as well as the most recent constraints from flavour physics, we present a detailed analysis of the current phenomenological status of the charged Higgs sector in a variety of wellmotivated two … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
181
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(193 citation statements)
references
References 190 publications
(167 reference statements)
11
181
0
1
Order By: Relevance
“…[33]. References [34,35] showed that the LHC searches for the charged Higgs fail to constrain the model for m H AE > 500 GeV. Therefore, the search channels for the charged Higgs are not included in this paper.…”
Section: B Theoretical and Experimental Constraintsmentioning
confidence: 99%
“…[33]. References [34,35] showed that the LHC searches for the charged Higgs fail to constrain the model for m H AE > 500 GeV. Therefore, the search channels for the charged Higgs are not included in this paper.…”
Section: B Theoretical and Experimental Constraintsmentioning
confidence: 99%
“…Interestingly, they found that masses below 1 TeV have not been excluded for color-octet scalars as is often claimed in the literature. For a variety of well-motivated 2HDMs, the authors in [55] found that charged-Higgs bosons as light as 75 GeV can still be compatible with all the results from direct charged and neutral Higgs boson searches at LEP and the LHC, as well as the most recent constraints from flavor physics, although this implies severely suppressed charged-Higgs couplings to all fermions. Thus, based on the above observations, we generate randomly numerical points for the model parameters as [34] From the above numerical results, we can make the following observations:…”
Section: Results In the 2hdms With Mfvmentioning
confidence: 82%
“…In a recent analysis, ATLAS has obtained limits for the H + → tb decay, for which the branching ratio can be sizable in our model [50]. Both searches put no relevant constraints on tan β for M H ± = 500 GeV [51].…”
Section: Jhep07(2018)107mentioning
confidence: 96%